Les écrivains issus de l’immigration face à la guerre d’Algérie : quelle mémoire pour quelles victimes ? - Crystel Pinçonnat (Amnis)
What are the traces left by the war of Algeria in narratives written by second-generation immigrant authors? Such is the main question raised by this article. However, far from only listing the different modes of inscription of the war in works of various statutes (story-testimony, fiction, and autobiography), this paper analyzes on one hand the way the writer remodels the community or domestic past, forging at the sametime a memory, that he transmits to its readers. On the other hand, the article also questions the aim of these narratives which, sometimes, choose the quasi-obliteration of violence, and sometimes on the contrary, try to write events for a long time repressed, as driven back from the French memory.